PERILAKU PARKIR LIAR MENGGUNAKAN SEM - Ramadani, Ahmad; Hakzah, Hakzah; Didi, Andi Bustan (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2025)
Jalan Jenderal Sudirman, Parepare City, South Sulawesi Province - Indonesia is a National road with a road type (4/2-T) with a length of about 3 km and an average width of 3.5 m. Along the road there are government offices, companies and housing that have limited parking space so that the road section is used as an illegal parking area. The purpose of this study focuses on the analysis of illegal parking behavior. The type of descriptive quantitative research uses SEM analysis. A total of 200 respondents based on the distribution of questionnaire data were selected randomly. The analysis used variables of attitude, subjective norms, behavioral control, economic factors and social factors. The results of the analysis of the attitude variable, the critical ratio (CR) value towards illegal parking was 2.460 1.97, p - value 0.014 0.05. Subjective norm variable, critical ratio 2.157 1.97 with a p - value of 0.031 0.05. Behavioral control variable n critical ratio value 2.648 1.97 with p - value 0.008 0.05. Economic factor variable n critical ratio value 4.056 1.97 with a p - value of 0.000 0.05. Social factor variable n critical ratio value 2.537 1.97 with p - value 0.011 0.05 . Indicates that all variables used in respondents have an effect on illegal parking along the road.